IMPLEMENTATION OF ROLE PLAYING METHODS BASED ON SOCIAL ISSUES ARROUND STUDENTS TO INCREASE STUDENTS COOPERATION ON SOCIAL RELATIONSHIP IN SOCIAL STUDIES LEARNING (CLASSROOM ACTION RESEARCH AT CLASS VII-C MUHAMMADIYAH 6 JUNIOR HIGH SCHOOL BANDUNG) - Pertiwi, Suci Febriyanti (International Journal Pedagogy of Social Studies, 2017)
Abstract-The purpose of this research is to increase cooperation among students through the role playing method on the students of class VIII-C Muhammadiyah 6 Junior High School Bandung academic year 2014/2015. This study uses a classroom action research approach. Subjects in this study were students in class VIII-C Muhammadiyah 6 Junior High School Bandung. of collecting data technique using Role Playing method and teacher achievement test. Action is done as much as 3 cycles, in one cycle done 2 times action. Data processing refers to qualitative procedures and changes in learning evaluation results before and after learning by using Role Playing method. The results showed: 1). The percentage of observation results of cooperation between friends on this 1st cycle has not been seen, because it is still within the range of "less" rating with the percentage of 38.1%. While the average learning achievement score of 74.5, although there is an increase but not showing the expected success rate because the acquisition of values above the minimum score only amounted to 9 people. 2). The result of student activity observation shows that the cooperation between students in cycle 2 is increased, and is in the range of "enough" assessment with the percentage of 68%, the average value obtained is 83.25, although there is improvement, indicating the expected success rate, there are students earning grades under the minimum score of 4 students. 3). The 3rd cycle shows a very high increase and is in the 'good' range with a percentage of 80% and an average value of 86.Keywords: cooperation, role playing